Penerapan Algoritma Decision Tree Untuk Memprediksi Penerima Bantuan Keluarga Harapan - Agus Bahtiar; Parasian DP Silitonga (STMIK IKMI Cirebon, 2020)
The Family of Hope Program (PKH) is a poverty reduction program in the education and public health aspects provided by the government either directly or indirectly. The government continues to make efforts in order to educate the community through social assistance programs to tackle the poor. In order to create a smart society, the government should make programs that are empowering so that people can solve their own problems. There are many in Indonesia who receive the family hope program (PKH), one of which is in the Cirebon district. Problems often occur with the empowerment assistance program from the government, one of which is the PKH assistance, which still does not target the residents who receive the assistance. The emergence of this problem, due to the ineffective data verification in determining which citizens are entitled to receive PKH assistance, this has resulted in many very poor people who do not receive PKH assistance and those classified as capable are still given PKH assistance. Therefore, it is necessary to conduct a study of PKH beneficiary data, so that the results of the analysis can be used as a reference for whether or not residents are eligible to receive PKH assistance. The research that was conducted to predict the data of recipients of the expected family assistance using the data mining classification method using the C4.5 algorithm. The results of the data mining process are used as evaluation material for the government. After testing with the C4.5 algorithm, the test results for the best parameter of the C4.5 algorithm are criterion = accuracy, confidence = 0.25 and a minimum gain = 0.1 to produce an accuracy value of 98.30%